Petrophysics and mass balance integration for alteration detection in orogenic gold exploration - Yasaman Nemati; J. Christian Dupuis; Benoit Quesnel; Bernard Giroux; Richard Smith; Georges Beaudoin (Journal of Applied Geophysics, 2026)

Continental Contrasts in Climate Extremes That Control Tree Fecundity - James S. Clark; Robert Andrus; Margarita Arianoutsou; Davide Ascoli; Yves Bergeron; Michal Bogdziewicz; Thomas Boivin; Raul Bonal; Thomas Caignard; Maxime Cailleret; Rafael Calama; J. Julio Camarero; et al. (Global Change Biology, 2026)
In 2023, more than half of olive harvests ( Olea europaea ) across Spain, Greece, and Türkiye were lost to drought. The same year late freeze destroyed 90% of the peach crop ( Prunus persica ) on the Georgia Piedmont and the apple crop ( Malus domestica ) in central New York, Vermont, and southern Quebec. Climate extremes now rank with the costliest threats to agriculture, but their role in forest recovery from diebacks that are happening globally is unknown for lack of tree fecundity estimates in forests. Tolerance of climate extremes could depend on past exposure but constrained by phylogenetic conservatism. We report a continental scale analysis of climate extremes and forest fecundity across North America and Europe showing that responses to late freeze and drought are happening now. Species differences are not explained by the traits typically included in ecological studies and they are weakly associated with phylogeny. Late freeze, that is, freezing temperatures that follow the onset of flower development in spring, is shown to be “normal” in North America, but not Europe, potentially explaining failed seed production due to delayed onset and the resultant shorter growing period by North American transplants dating back at least to the 18th century. Drought has thus far had the greatest impacts in dry forested regions, but here too, species differences are not explained by traditional trait values. If responses have been buffered from drought and late freeze by past exposure, acclimation and local adaptation prove inadequate as extremes intensify.

Clinical spectrum of ICU-acquired invasive pulmonary aspergillosis according to SARS-CoV2 infection: a multicenter prospective cohort study - Florian Reizine; Mattéo Mauget; Nicolas Massart; Yannick Fedun; Anaïs Machut; Charles-Hervé Vacheron; Anne Savey; Arnaud Friggeri; Alain Lepape; Melissa Abbes; Abdelkrim Abdelmalek; Francoise Adema; et al. (European Journal of Clinical Microbiology & Infectious Diseases, 2026)

Integrating prior information for improving 3D model-driven GAI estimation with application to wheat crops - Mingxia Dong; Shouyang Liu; Marie Weiss; Aojie Yin; Chen Zhu; Benoit de Solan; Wei Guo; Fernandes Richard; Wenjuan Li; Xia Yao; James Burridge; Zhen Chen; et al. (Remote Sensing of Environment, 2026)

Plant Trait Matching Occurs in Facilitative Interactions Across Global Drylands - Imke C. Smit; Peter C. le Roux; Santiago Soliveres; Nicolas Gross; Yoann Le Bagousse‐Pinguet; Hugo Saiz; Mehdi Abedi; Rodrigo Ahumada; Antonio I. Arroyo; Sergio Asensio; Richard Benoit; Niels Blaum; et al. (Global Ecology and Biogeography, 2025)
Aim Plant functional traits can influence interaction outcomes between nurse and target plants through a “functional trait match”, which occurs when the traits of nurse plants ameliorate their environment, and target plants possess traits that allow them to benefit from this ameliorated environment. We investigated how the traits of putative nurse species affect interaction outcomes across global drylands and determined the functional match that promotes facilitation. We also investigated how grazing pressure and global climatic and edaphic gradients affected this trait match. Location Global drylands. Time Period 2016–2019. Major Taxa Studied Vascular plants. Methods We used a collaborative survey conducted across 29 sites from five continents, where we gathered in situ co‐occurrences of dominant species (‘nurses’) and other vascular plant species, as well as their functional traits [plant height and leaf dry matter content (LDMC)]. Climate, edaphic variables and grazing pressure were measured in situ or extracted from databases. We used a model building approach to determine the effect of dominant plant traits on interaction outcomes, and how the functional trait match between nurse and target species is affected by environmental variables. Results Tall dominant plants with conservative leaves generally had a greater positive effect on species richness and cover beneath their canopies, but these effects were strongly modulated by grazing pressure and soil pH. Target plants that were significantly associated with dominant plants tended to be shorter, and have more acquisitive leaves than dominant plants, regardless of environmental conditions. However, the difference in height and LDMC between dominant plants and negatively associated target plants was strongly affected by environmental conditions. Main Conclusions Functional traits play a significant role in determining interaction outcomes between dryland plants. Facilitation in drylands is driven by a conservative‐acquisitive trait match, a pattern observed regardless of grazing pressure, climate and soil conditions.

Late 21st‐Century Climate and Land Use Driven Loss of Plant Diversity in African Mountains - João de Deus Vidal Junior; Alexandre Antonelli; Clinton Carbutt; Vincent Ralph Clark; Tobias Fremout; Christopher Chapano; Inês Chelene; David Chuba; Tadesse Woldemariam Gole; Clayton Langa; Benoit Loeuille; Ermias Lulekal Molla; et al. (Global Change Biology, 2025)
With the 1.5°C–5°C increase in global temperature projected for this century, many plant species are expected to shift their distribution ranges to track their environmental requirements. Across several mountain regions, responses to climate change like upslope shifts may result in accelerated rates of species turnover, species richness increases in upper montane belts, and amplified habitat losses. Yet, evidence of how such processes may influence plant diversity in Africa is still scarce. Here, using a species distribution modeling approach, we quantify and map how different scenarios of climatic and land‐use changes may affect plant species ranges in African mountains. Using individually tuned models and dispersal buffers, we compared distribution losses and potential expansion through dispersal across 607 vascular plant species under three shared socioeconomic pathways for the end of the century. Our projections indicate that keeping warming under 2°C until 2100 under a sustainability scenario (SSP1.26), almost half (49.3%) of the species would experience a contraction in suitable areas, compared to 71%–75.6% in case these targets are not met (SSP3.70 and SSP5.85). Among these losses, mean contractions between 19% and 50.4% are predicted depending on the scenario. We project rates of upslope shifts that may be up to three times higher than the global calculated average. Contractions will be higher for species occurring at upper elevations, and trees and shrubs will show lower declines. Our findings align with previously reported trends of upslope shifts of species distributions but suggest that accelerated rates of change may limit the capacity of some species to track their niche based solely on their natural dispersal capacity. This implies that further efforts to improve habitat connectivity, restoration, and assisted migration may be necessary.

Effect of freeze-thaw cycles on engineering properties of nano-SiO2 enhanced microbially induced calcium carbonate precipitation in kaolinite clay - Sara Ghalandarzadeh; Benoit Courcelles; Richard Boudreault; Lukas U. Arenson; Pooneh Maghoul (Cold Regions Science and Technology, 2025)

BioTIME 2.0: Expanding and Improving a Database of Biodiversity Time Series - Maria Dornelas; Laura H. Antão; Amanda E. Bates; Viviana Brambilla; Jonathan M. Chase; Cher F. Y. Chow; Ada Fontrodona‐Eslava; Anne E. Magurran; Inês S. Martins; Faye Moyes; Alban Sagouis; Samuel Adu‐Acheampong; et al. (Global Ecology and Biogeography, 2025)
Motivation Here, we make available a second version of the BioTIME database, which compiles records of abundance estimates for species in sample events of ecological assemblages through time. The updated version expands version 1.0 of the database by doubling the number of studies and includes substantial additional curation to the taxonomic accuracy of the records, as well as the metadata. Moreover, we now provide an R package (BioTIMEr) to facilitate use of the database. Main Types of Variables Included The database is composed of one main data table containing the abundance records and 11 metadata tables. The data are organised in a hierarchy of scales where 11,989,233 records are nested in 1,603,067 sample events, from 553,253 sampling locations, which are nested in 708 studies. A study is defined as a sampling methodology applied to an assemblage for a minimum of 2 years. Spatial Location and Grain Sampling locations in BioTIME are distributed across the planet, including marine, terrestrial and freshwater realms. Spatial grain size and extent vary across studies depending on sampling methodology. We recommend gridding of sampling locations into areas of consistent size. Time Period and Grain The earliest time series in BioTIME start in 1874, and the most recent records are from 2023. Temporal grain and duration vary across studies. We recommend doing sample‐level rarefaction to ensure consistent sampling effort through time before calculating any diversity metric. Major Taxa and Level of Measurement The database includes any eukaryotic taxa, with a combined total of 56,400 taxa. Software Format csv and. SQL.

Observational Assessment of Changes in Earth’s Energy Imbalance Since 2000 - Norman G. Loeb; Seung-Hee Ham; Richard P. Allan; Tyler J. Thorsen; Benoit Meyssignac; Seiji Kato; Gregory C. Johnson; John M. Lyman (Surveys in Geophysics, 2024)
Satellite observations from the Clouds and the Earth’s Radiant Energy System show that Earth’s energy imbalance has doubled from 0.5 ± 0.2 Wm −2 during the first 10 years of this century to 1.0 ± 0.2 Wm − 2 during the past decade. The increase is the result of a 0.9 ± 0.3 Wm −2 increase absorbed solar radiation (ASR) that is partially offset by a 0.4 ± 0.25 Wm −2 increase in outgoing longwave radiation (OLR). Despite marked differences in ASR and OLR trends during the hiatus (2000–2010), transition-to-El Niño (2010–2016) and post-El Niño (2016–2022) periods, trends in net top-of-atmosphere flux (NET) remain within 0.1 Wm −2 per decade of one another, implying a steady acceleration of climate warming. Northern and southern hemisphere trends in NET are consistent to 0.06 ± 0.31 Wm −2 per decade due to a compensation between weak ASR and OLR hemispheric trend differences of opposite sign. We find that large decreases in stratocumulus and middle clouds over the sub-tropics and decreases in low and middle clouds at mid-latitudes are the primary reasons for increasing ASR trends in the northern hemisphere (NH). These changes are especially large over the eastern and northern Pacific Ocean, and coincide with large increases in sea-surface temperature (SST). The decrease in cloud fraction and higher SSTs over the NH sub-tropics lead to a significant increase in OLR from cloud-free regions, which partially compensate for the NH ASR increase. Decreases in middle cloud reflection and a weaker reduction in low-cloud reflection account for the increase in ASR in the southern hemisphere, while OLR changes are weak. Changes in cloud cover in response to SST increases imply a feedback to climate change yet a contribution from radiative forcing or internal variability cannot be ruled out.

The Relationship Between Maturation Size and Maximum Tree Size From Tropical to Boreal Climates - Valentin Journé; Michał Bogdziewicz; Benoit Courbaud; Georges Kunstler; Tong Qiu; Marie‐Claire Aravena Acuña; Davide Ascoli; Yves Bergeron; Daniel Berveiller; Thomas Boivin; Raul Bonal; Thomas Caignard; et al. (Ecology Letters, 2024)
The fundamental trade‐off between current and future reproduction has long been considered to result in a tendency for species that can grow large to begin reproduction at a larger size. Due to the prolonged time required to reach maturity, estimates of tree maturation size remain very rare and we lack a global view on the generality and the shape of this trade‐off. Using seed production from five continents, we estimate tree maturation sizes for 486 tree species spanning tropical to boreal climates. Results show that a species' maturation size increases with maximum size, but in a non‐proportional way: the largest species begin reproduction at smaller sizes than would be expected if maturation were simply proportional to maximum size. Furthermore, the decrease in relative maturation size is steepest in cold climates. These findings on maturation size drivers are key to accurately represent forests' responses to disturbance and climate change.

Modeling the fate of viruses in aquifers: Multi-kinetics reactive transport, risk assessment, and governing parameters - Silvain Rafini; Romain Chesnaux; Kim Maren Lompe; Benoit Barbeau; Dominique Claveau-Mallet; Dominique Richard (Science of The Total Environment, 2023)

Development of a mechanistic model for analyzing avian reproduction data for pesticide risk assessment - Marie Trijau; Benoit Goussen; Richard Brain; Jonathan Maul; Nika Galic (Environmental Pollution, 2023)

Is a dissipation half-life of 5 years for chlordecone in soils of the French West Indies relevant? - Pierre-Loïc Saaidi; Olivier Grünberger; Anatja Samouëlian; Yves Le Roux; Antoine Richard; Damien A. Devault; Cyril Feidt; Pierre Benoit; Olivier Evrard; Gwenaël Imfeld; Christophe Mouvet; Marc Voltz (Environmental Pollution, 2023)

Linking seed size and number to trait syndromes in trees - Michal Bogdziewicz; Marie‐Claire Aravena Acuña; Robert Andrus; Davide Ascoli; Yves Bergeron; Daniel Brveiller; Thomas Boivin; Raul Bonal; Thomas Caignard; Maxime Cailleret; Rafael Calama; Sergio Donoso Calderon; et al. (Global Ecology and Biogeography, 2023)
Aim Our understanding of the mechanisms that maintain forest diversity under changing climate can benefit from knowledge about traits that are closely linked to fitness. We tested whether the link between traits and seed number and seed size is consistent with two hypotheses, termed the leaf economics spectrum and the plant size syndrome, or whether reproduction represents an independent dimension related to a seed size–seed number trade‐off. Location Most of the data come from Europe, North and Central America and East Asia. A minority of the data come from South America, Africa and Australia. Time period 1960–2022. Major taxa studied Trees. Methods We gathered 12 million observations of the number of seeds produced in 784 tree species. We estimated the number of seeds produced by individual trees and scaled it up to the species level. Next, we used principal components analysis and generalized joint attribute modelling (GJAM) to map seed number and size on the tree traits spectrum. Results Incorporating seed size and number into trait analysis while controlling for environment and phylogeny with GJAM exposes relationships in trees that might otherwise remain hidden. Production of the large total biomass of seeds [product of seed number and seed size; hereafter, species seed productivity (SSP)] is associated with high leaf area, low foliar nitrogen, low specific leaf area (SLA) and dense wood. Production of high seed numbers is associated with small seeds produced by nutrient‐demanding species with softwood, small leaves and high SLA. Trait covariation is consistent with opposing strategies: one fast‐growing, early successional, with high dispersal, and the other slow‐growing, stress‐tolerant, that recruit in shaded conditions. Main conclusions Earth system models currently assume that reproductive allocation is indifferent among plant functional types. Easily measurable seed size is a strong predictor of the seed number and species seed productivity. The connection of SSP with the functional traits can form the first basis of improved fecundity prediction across global forests.

The ecologically relevant genetics of plant–plant interactions - Claude Becker; Richard Berthomé; Philippe Delavault; Timothée Flutre; Hélène Fréville; Stéphanie Gibot-Leclerc; Valérie Le Corre; Jean-Benoit Morel; Nathalie Moutier; Stéphane Muños; Céline Richard-Molard; James Westwood; et al. (Trends in Plant Science, 2023)

AMAZONIA CAMTRAP: A data set of mammal, bird, and reptile species recorded with camera traps in the Amazon forest - Ana Carolina Antunes; Anelise Montanarin; Diogo Maia Gräbin; Erison Carlos dos Santos Monteiro; Fernando Ferreira de Pinho; Guilherme Costa Alvarenga; Jorge Ahumada; Robert B. Wallace; Emiliano Esterci Ramalho; Adrian Paul Ashton Barnett; Alex Bager; Alexandre Martins Costa Lopes; et al. (Ecology, 2022)
The Amazon forest has the highest biodiversity on Earth. However, information on Amazonian vertebrate diversity is still deficient and scattered across the published, peer‐reviewed, and gray literature and in unpublished raw data. Camera traps are an effective non‐invasive method of surveying vertebrates, applicable to different scales of time and space. In this study, we organized and standardized camera trap records from different Amazon regions to compile the most extensive data set of inventories of mammal, bird, and reptile species ever assembled for the area. The complete data set comprises 154,123 records of 317 species (185 birds, 119 mammals, and 13 reptiles) gathered from surveys from the Amazonian portion of eight countries (Brazil, Bolivia, Colombia, Ecuador, French Guiana, Peru, Suriname, and Venezuela). The most frequently recorded species per taxa were: mammals: Cuniculus paca (11,907 records); birds: Pauxi tuberosa (3713 records); and reptiles: Tupinambis teguixin (716 records). The information detailed in this data paper opens up opportunities for new ecological studies at different spatial and temporal scales, allowing for a more accurate evaluation of the effects of habitat loss, fragmentation, climate change, and other human‐mediated defaunation processes in one of the most important and threatened tropical environments in the world. The data set is not copyright restricted; please cite this data paper when using its data in publications and we also request that researchers and educators inform us of how they are using these data.

Globally, tree fecundity exceeds productivity gradients - Valentin Journé; Robert Andrus; Marie‐Claire Aravena; Davide Ascoli; Roberta Berretti; Daniel Berveiller; Michal Bogdziewicz; Thomas Boivin; Raul Bonal; Thomas Caignard; Rafael Calama; Jesús Julio Camarero; et al. (Ecology Letters, 2022)
Lack of tree fecundity data across climatic gradients precludes the analysis of how seed supply contributes to global variation in forest regeneration and biotic interactions responsible for biodiversity. A global synthesis of raw seedproduction data shows a 250‐fold increase in seed abundance from cold‐dry to warm‐wet climates, driven primarily by a 100‐fold increase in seed production for a given tree size. The modest (threefold) increase in forest productivity across the same climate gradient cannot explain the magnitudes of these trends. The increase in seeds per tree can arise from adaptive evolution driven by intense species interactions or from the direct effects of a warm, moist climate on tree fecundity. Either way, the massive differences in seed supply ramify through food webs potentially explaining a disproportionate role for species interactions in the wet tropics.

Threats of illegal, unregulated, and unreported fishing to biodiversity and food security in the Republic of the Congo - Philip D. Doherty; Benoit C. Atsango; Gaston Ngassiki; Appolinaire Ngouembe; Nathalie Bréheret; Eva Chauvet; Brendan J. Godley; Lucie Machin; Baudelaire Dissondet Moundzoho; Richard J. Parnell; Kristian Metcalfe (Conservation Biology, 2021)
Illegal, unregulated, and unreported (IUU) fishing poses a major threat to effective management of marine resources, affecting biodiversity and communities dependent on these coastal resources. Spatiotemporal patterns of industrial fisheries in developing countries are often poorly understood, and global efforts to describe spatial patterns of fishing vessel activity are currently based on automatic identification system (AIS) data. However, AIS is often not a legal requirement on fishing vessels, likely resulting in underestimates of the scale and distribution of legal and illegal fishing activity, which could have significant ramifications for targeted enforcement efforts and the management of fisheries resources. To help address this knowledge gap, we analyzed 3 years of vessel monitoring system (VMS) data in partnership with the national fisheries department in the Republic of the Congo to describe the behavior of national and distant‐water industrial fleets operating in these waters. We found that the spatial footprint of the industrial fisheries fleet encompassed over one‐quarter of the Exclusive Economic Zone. On average, 73% of fishing activity took place on the continental shelf (waters shallower than 200 m). Our findings highlight that VMS is not acting as a deterrent or being effectively used as a proactive management tool. As much as 33% (13% on average) of fishing effort occurred in prohibited areas set aside to protect biodiversity, including artisanal fisheries resources, and the distant‐water fleet responsible for as much as 84% of this illegal activity. Given the growth in industrial and distant‐water fleets across the region, as well as low levels of management and enforcement, these findings highlight that there is an urgent need for the global community to help strengthen regional and national capacity to analyze national scale data sets if efforts to combat IUU fishing are to be effective.

Cross-tolerance and transcriptional shifts underlying abiotic stress in the seabird tick, Ixodes uriae - Benjamin Davies; Andrew J. Rosendale; Josiah D. Gantz; Richard E. Lee; David L. Denlinger; Joshua B. Benoit (Polar Biology, 2021)

The climatic debt is growing in the understorey of temperate forests: Stand characteristics matter - Benoit Richard; Jean‐Luc Dupouey; Emmanuel Corcket; Didier Alard; Frédéric Archaux; Michaël Aubert; Vincent Boulanger; François Gillet; Estelle Langlois; Sébastien Macé; Pierre Montpied; Thérèse Beaufils; et al. (Global Ecology and Biogeography, 2021)
Aim Climate warming reshuffles biological assemblages towards less cold‐adapted but more warm‐adapted species, a process coined thermophilization. However, the velocity at which this process is happening generally lags behind the velocity of climate change, generating a climatic debt the temporal dynamics of which remain misunderstood. Relying on high‐resolution time series of vegetation data from a long‐term monitoring network of permanent forest plots, we aim at quantifying the temporal dynamics – up to a yearly resolution – of the climatic debt in the understorey of temperate forests before identifying the key determinants that modulate it. Location France. Time period 1995–2017. Taxa studied Vascular plants. Methods We used the community temperature index (CTI) to produce a time series of understorey plant community thermophilization, which we subsequently compared to a time series of mean annual temperature changes over the same period and for the same sites. The direction and magnitude of the difference (i.e., the climatic debt) was finally analysed using linear mixed‐effect models to assess the relative contributions of abiotic and biotic determinants, including forest stand characteristics. Results We found a significant increase in CTI values over time (0.08–0.09 °C/decade), whereas the velocity of mean annual temperature changes was three times higher over the same period (0.22–0.28 °C/decade). Hence, the climatic debt increased over time and was greater in forest stands with higher basal area or older trees as well as under warmer macroclimate. By contrast, a greater frequency of anthropogenic disturbances decreased the climatic debt, while natural disturbances and herbivory had no impact. Conclusions Although often overlooked in understanding the climatic debt of forest biodiversity, changes in forest stand characteristics may modulate the climatic debt by locally modifying microclimatic conditions. Notably, the buffering effect of the upper canopy layer implies microclimate dynamics that may provide more time for understorey plant communities to locally adapt.

NEOTROPICAL CARNIVORES: a data set on carnivore distribution in the Neotropics - Mariana Nagy‐Reis; Júlia Emi de Faria Oshima; Claudia Zukeran Kanda; Francesca Belem Lopes Palmeira; Fabiano Rodrigues de Melo; Ronaldo Gonçalves Morato; Lilian Bonjorne; Marcelo Magioli; Caroline Leuchtenberger; Fabio Rohe; Frederico Gemesio Lemos; Felipe Martello; et al. (Ecology, 2020)
Mammalian carnivores are considered a key group in maintaining ecological health and can indicate potential ecological integrity in landscapes where they occur. Carnivores also hold high conservation value and their habitat requirements can guide management and conservation plans. The order Carnivora has 84 species from 8 families in the Neotropical region: Canidae; Felidae; Mephitidae; Mustelidae; Otariidae; Phocidae; Procyonidae; and Ursidae. Herein, we include published and unpublished data on native terrestrial Neotropical carnivores (Canidae; Felidae; Mephitidae; Mustelidae; Procyonidae; and Ursidae). NEOTROPICAL CARNIVORES is a publicly available data set that includes 99,605 data entries from 35,511 unique georeferenced coordinates. Detection/non‐detection and quantitative data were obtained from 1818 to 2018 by researchers, governmental agencies, non‐governmental organizations, and private consultants. Data were collected using several methods including camera trapping, museum collections, roadkill, line transect, and opportunistic records. Literature (peer‐reviewed and grey literature) from Portuguese, Spanish and English were incorporated in this compilation. Most of the data set consists of detection data entries (n = 79,343; 79.7%) but also includes non‐detection data (n = 20,262; 20.3%). Of those, 43.3% also include count data (n = 43,151). The information available in NEOTROPICAL CARNIVORES will contribute to macroecological, ecological, and conservation questions in multiple spatio‐temporal perspectives. As carnivores play key roles in trophic interactions, a better understanding of their distribution and habitat requirements are essential to establish conservation management plans and safeguard the future ecological health of Neotropical ecosystems. Our data paper, combined with other large‐scale data sets, has great potential to clarify species distribution and related ecological processes within the Neotropics. There are no copyright restrictions and no restriction for using data from this data paper, as long as the data paper is cited as the source of the information used. We also request that users inform us of how they intend to use the data.

Correction to: Documenting lemming population change in the Arctic: Can we detect trends? - Dorothée Ehrich; Niels M. Schmidt; Gilles Gauthier; Ray Alisauskas; Anders Angerbjörn; Karin Clark; Frauke Ecke; Nina E. Eide; Erik Framstad; Jay Frandsen; Alastair Franke; Olivier Gilg; et al. (Ambio, 2020)

Documenting lemming population change in the Arctic: Can we detect trends? - Dorothée Ehrich; Niels M. Schmidt; Gilles Gauthier; Ray Alisauskas; Anders Angerbjörn; Karin Clark; Frauke Ecke; Nina E. Eide; Erik Framstad; Jay Frandsen; Alastair Franke; Olivier Gilg; et al. (Ambio, 2020)

Metabolomics and fish nutrition: a review in the context of sustainable feed development - Simon Roques; Catherine Deborde; Nadège Richard; Sandrine Skiba‐Cassy; Annick Moing; Benoit Fauconneau (Reviews in Aquaculture, 2020)
Aquaculture is facing a strategic challenge to improve feed suitability and support the global increase in fish production. Improvements in diet formulation for sustainable nutritional strategies have focused to date on the partial substitution of marine resources by plant resources but will now include other alternative feedstuffs. Growth trials and body composition data provide valuable indicators of fish nutritional status, while omics technologies may contribute to a better understanding of fish nutrition and help to demonstrate how feed and nutrients act in fish metabolism. Metabolomic approaches give an insight into fish metabolism through a non‐targeted analysis of metabolites in tissues or biofluids that involve multiple factors affecting fish, such as nutrition. In this review, we highlight the outcomes of publications in metabolomics applied to fish nutrition. We explain the concept of metabolomics and discuss specific technical considerations related to sample type, sampling and sample preparation. We show how metabolomic studies help to elucidate the impact of nutrition on fish fillet composition and fish metabolism. Finally, we describe the potential applications of metabolomic approaches for the non‐invasive monitoring of fish nutritional status.

TRY plant trait database – enhanced coverage and open access - Jens Kattge; Gerhard Bönisch; Sandra Díaz; Sandra Lavorel; Iain Colin Prentice; Paul Leadley; Susanne Tautenhahn; Gijsbert D. A. Werner; Tuomas Aakala; Mehdi Abedi; Alicia T. R. Acosta; George C. Adamidis; et al. (Global Change Biology, 2020)
Plant traits—the morphological, anatomical, physiological, biochemical and phenological characteristics of plants—determine how plants respond to environmental factors, affect other trophic levels, and influence ecosystem properties and their benefits and detriments to people. Plant trait data thus represent the basis for a vast area of research spanning from evolutionary biology, community and functional ecology, to biodiversity conservation, ecosystem and landscape management, restoration, biogeography and earth system modelling. Since its foundation in 2007, the TRY database of plant traits has grown continuously. It now provides unprecedented data coverage under an open access data policy and is the main plant trait database used by the research community worldwide. Increasingly, the TRY database also supports new frontiers of trait‐based plant research, including the identification of data gaps and the subsequent mobilization or measurement of new data. To support this development, in this article we evaluate the extent of the trait data compiled in TRY and analyse emerging patterns of data coverage and representativeness. Best species coverage is achieved for categorical traits—almost complete coverage for ‘plant growth form’. However, most traits relevant for ecology and vegetation modelling are characterized by continuous intraspecific variation and trait–environmental relationships. These traits have to be measured on individual plants in their respective environment. Despite unprecedented data coverage, we observe a humbling lack of completeness and representativeness of these continuous traits in many aspects. We, therefore, conclude that reducing data gaps and biases in the TRY database remains a key challenge and requires a coordinated approach to data mobilization and trait measurements. This can only be achieved in collaboration with other initiatives.

Seismic properties of gabbroic sections in oceanic core complexes: constraints from seafloor drilling - Donna K. Blackman; Natsue Abe; Richard L. Carlson; Gilles Guerin; Benoit Ildefonse; Amber Kumpf (Marine Geophysical Research, 2019)

The Antarctic mite, Alaskozetes antarcticus, shares bacterial microbiome community membership but not abundance between adults and tritonymphs - Christopher J. Holmes; Emily C. Jennings; J. D. Gantz; Drew Spacht; Austin A. Spangler; David L. Denlinger; Richard E. Lee; Trinity L. Hamilton; Joshua B. Benoit (Polar Biology, 2019)

Voluntary Restoration: Mitigation's Silent Partner in the Quest to Reverse Coastal Wetland Loss in the USA - Rachel K. Gittman; Christopher J. Baillie; Katie K. Arkema; Richard O. Bennett; Jeff Benoit; Seth Blitch; Julien Brun; Anthony Chatwin; Allison Colden; Alyssa Dausman; Bryan DeAngelis; Nathaniel Herold; et al. (Frontiers in Marine Science, 2019)

Towards Comprehensive Observing and Modeling Systems for Monitoring and Predicting Regional to Coastal Sea Level - Rui M. Ponte; Mark Carson; Mauro Cirano; Catia M. Domingues; Svetlana Jevrejeva; Marta Marcos; Gary Mitchum; R. S. W. van de Wal; Philip L. Woodworth; Michaël Ablain; Fabrice Ardhuin; Valérie Ballu; et al. (Frontiers in Marine Science, 2019)

Sex- and developmental-specific transcriptomic analyses of the Antarctic mite, Alaskozetes antarcticus, reveal transcriptional shifts underlying oribatid mite reproduction - Hannah E. Meibers; Geoffrey Finch; Robert T. Gregg; Sierra Glenn; Keavash D. Assani; Emily C. Jennings; Benjamin Davies; Andrew J. Rosendale; Christopher J. Holmes; J. D. Gantz; Drew E. Spacht; Richard E. Lee; et al. (Polar Biology, 2019)

Pan‐tropical prediction of forest structure from the largest trees - Jean‐François Bastin; Ervan Rutishauser; James R. Kellner; Sassan Saatchi; Raphael Pélissier; Bruno Hérault; Ferry Slik; Jan Bogaert; Charles De Cannière; Andrew R. Marshall; John Poulsen; Patricia Alvarez‐Loyayza; et al. (Global Ecology and Biogeography, 2018)
Aim Large tropical trees form the interface between ground and airborne observations, offering a unique opportunity to capture forest properties remotely and to investigate their variations on broad scales. However, despite rapid development of metrics to characterize the forest canopy from remotely sensed data, a gap remains between aerial and field inventories. To close this gap, we propose a new pan‐tropical model to predict plot‐level forest structure properties and biomass from only the largest trees. Location Pan‐tropical. Time period Early 21st century. Major taxa studied Woody plants. Methods Using a dataset of 867 plots distributed among 118 sites across the tropics, we tested the prediction of the quadratic mean diameter, basal area, Lorey's height, community wood density and aboveground biomass (AGB) from the i th largest trees. Results Measuring the largest trees in tropical forests enables unbiased predictions of plot‐ and site‐level forest structure. The 20 largest trees per hectare predicted quadratic mean diameter, basal area, Lorey's height, community wood density and AGB with 12, 16, 4, 4 and 17.7% of relative error, respectively. Most of the remaining error in biomass prediction is driven by differences in the proportion of total biomass held in medium‐sized trees (50–70 cm diameter at breast height), which shows some continental dependency, with American tropical forests presenting the highest proportion of total biomass in these intermediate‐diameter classes relative to other continents. Main conclusions Our approach provides new information on tropical forest structure and can be used to generate accurate field estimates of tropical forest carbon stocks to support the calibration and validation of current and forthcoming space missions. It will reduce the cost of field inventories and contribute to scientific understanding of tropical forest ecosystems and response to climate change.

One-Single Extraction Procedure for the Simultaneous Determination of a Wide Range of Polar and Nonpolar Organic Contaminants in Seawater - Vincent Fauvelle; Javier Castro-Jiménez; Natascha Schmidt; Benoit Carlez; Christos Panagiotopoulos; Richard Sempéré (Frontiers in Marine Science, 2018)

Assessing mid-latitude dynamics in extreme event attribution systems - Daniel Mitchell; Paolo Davini; Ben Harvey; Neil Massey; Karsten Haustein; Tim Woollings; Richard Jones; Fredi Otto; Benoit Guillod; Sarah Sparrow; David Wallom; Myles Allen (Climate Dynamics, 2017)

Pedigree Reconstruction with Genome-Wide Markers in Potato - Jeffrey B. Endelman; Cari A. Schmitz Carley; David S. Douches; Joseph J. Coombs; Benoit Bizimungu; Walter S. De Jong; Kathleen G. Haynes; David G. Holm; J. Creighton Miller; Richard G. Novy; Jiwan P. Palta; David L. Parish; et al. (American Journal of Potato Research, 2017)

How the truffle got its mate: insights from genetic structure in spontaneous and planted Mediterranean populations of Tuber melanosporum - E. Taschen; F. Rousset; M. Sauve; L. Benoit; M.‐P. Dubois; F. Richard; M.‐A. Selosse (Molecular Ecology, 2016)
The life cycles and dispersal of edible fungi are still poorly known, thus limiting our understanding of their evolution and domestication. The prized Tuber melanosporum produces fruitbodies (fleshy organs where meiospores mature) gathered in natural, spontaneously inoculated forests or harvested in plantations of nursery‐inoculated trees. Yet, how fruitbodies are formed remains unclear, thus limiting yields, and how current domestication attempts affect population genetic structure is overlooked. Fruitbodies result from mating between two haploid individuals: the maternal parent forms the flesh and the meiospores, while the paternal parent only contributes to the meiospores. We analyzed the genetic diversity of T. melanosporum comparatively in spontaneous forests vs. plantations, using SSR polymorphism of 950 samples from South‐East France. All populations displayed strong genetic isolation by distance at the metric scale, possibly due to animal dispersal, meiospore persistence in soil, and/or exclusion of unrelated individuals by vegetative incompatibility. High inbreeding was consistently found, suggesting that parents often develop from meiospores produced by the same fruitbody. Unlike maternal genotypes, paternal mycelia contributed to few fruitbodies each, did not persist over years, and were undetectable on tree mycorrhizae. Thus, we postulate that germlings from the soil spore bank act as paternal partners. Paternal genetic diversity and outbreeding were higher in plantations than in spontaneous truffle‐grounds, perhaps because truffle growers disperse fruitbodies to maintain inoculation in plantations. However, planted and spontaneous populations were not genetically isolated, so that T. melanosporum illustrates an early step of domestication where genetic structure remains little affected.

Old nurses always die: impacts of nurse age on local plant richness - Fateh Amghar; Estelle Forey; Benoit Richard; Blaise Touzard; Souhila Laddada; Lakhdar Brouri; Estelle Langlois; Pierre Margerie (Plant Ecology, 2016)

The harlequin ladybird, Harmonia axyridis: global perspectives on invasion history and ecology - Helen E. Roy; Peter M. J. Brown; Tim Adriaens; Nick Berkvens; Isabel Borges; Susana Clusella-Trullas; Richard F. Comont; Patrick De Clercq; Rene Eschen; Arnaud Estoup; Edward W. Evans; Benoit Facon; et al. (Biological Invasions, 2016)

Lead exposure through consumption of big game meat in Quebec, Canada: risk assessment and perception - Richard Coovi Fachehoun; Benoit Lévesque; Pierre Dumas; Antoine St-Louis; Marjolaine Dubé; Pierre Ayotte (Food Additives & Contaminants: Part A, 2015)

Impacts of Coastal Acidification on the Pacific Northwest Shellfish Industry and Adaptation Strategies Implemented in Response - Alan Barton; George Waldbusser; Richard Feely; Stephen Weisberg; Jan Newton; Burke Hales; Sue Cudd; Benoit Eudeline; Chris Langdon; Ian Jefferds; Teri King; Andy Suhrbier; et al. (Oceanography, 2015)

Biological invasions in soil: DNA barcoding as a monitoring tool in a multiple taxa survey targeting European earthworms and springtails in North America - David Porco; Thibaud Decaëns; Louis Deharveng; Samuel W. James; Dariusz Skarżyński; Christer Erséus; Kevin R. Butt; Benoit Richard; Paul D. N. Hebert (Biological Invasions, 2013)

Bile salts induce long polar fimbriae expression favouring Crohn's disease‐associated adherent‐invasive Escherichia coli interaction with Peyer's patches - Benoit Chassaing; Lucie Etienne‐Mesmin; Richard Bonnet; Arlette Darfeuille‐Michaud (Environmental Microbiology, 2013)
Summary Ileal lesions of patients with Crohn's disease are colonized by adherent‐invasive Escherichia coli (AIEC). The earliest lesions of recurrent Crohn's disease are erosions of Peyer's patches (PP). We recently reported the presence of a functional lpf operon in AIEC, encoding long polar fimbriae (LPF), that allows AIEC bacteria to interact with PP and to translocate across M cells. The aim of this study was to analyse the effect of gastrointestinal conditions on LPF expression in AIEC strains. The LF82 bacterial growth in an acid pH medium or at high osmolarity medium had no effect on lpf transcription level, in contrast to bacterial growth in the presence of bile salts, which promoted activation of lpf transcription. When cultured in the presence of bile salt, LF82 wild‐type bacteria, but not the isogenic mutant deleted for lpfA , exhibited a higher level of interaction with PP and a higher level of translocation through M cell monolayers. The FhlA transcriptional factor was found to be a key bacterial regulator at the origin of LPF expression in the presence of bile salts.

Food sources used by sediment meiofauna in an intertidal Zostera noltii seagrass bed: a seasonal stable isotope study - Benoit Lebreton; Pierre Richard; Robert Galois; Gilles Radenac; Amel Brahmia; Géraldine Colli; Marig Grouazel; Cyril André; Gaël Guillou; Gérard F. Blanchard (Marine Biology, 2012)

Optimized assay and storage conditions for enzyme activity profiling of ectomycorrhizae - Karin Pritsch; Pierre Emanuel Courty; Jean-Louis Churin; Benoit Cloutier-Hurteau; Muhammad Arif Ali; Coralie Damon; Myriam Duchemin; Simon Egli; Jana Ernst; Laurence Fraissinet-Tachet; Francisco Kuhar; Elvira Legname; et al. (Mycorrhiza, 2011)

Dehydration, rehydration, and overhydration alter patterns of gene expression in the Antarctic midge, Belgica antarctica - Giancarlo Lopez-Martinez; Joshua B. Benoit; Joseph P. Rinehart; Michael A. Elnitsky; Richard E. Lee; David L. Denlinger (Journal of Comparative Physiology B, 2009)

ps-2, the gene responsible for functional sterility in tomato, due to non-dehiscent anthers, is the result of a mutation in a novel polygalacturonase gene - Benoit Gorguet; Danny Schipper; André van Lammeren; Richard G. F. Visser; Adriaan W. van Heusden (Theoretical and Applied Genetics, 2009)

The seabird tick, Ixodes uriae, uses uric acid in penguin guano as a kairomone and guanine in tick feces as an assembly pheromone on the Antarctic Peninsula - Joshua B. Benoit; Giancarlo Lopez-Martinez; Seth A. Philips; Michael A. Elnitsky; Jay A. Yoder; Richard E. Lee; David L. Denlinger (Polar Biology, 2008)

Extremely large aggregations of collembolan eggs on Humble Island, Antarctica: a response to early seasonal warming? - Glen G. Schulte; Michael A. Elnitsky; Joshua B. Benoit; David L. Denlinger; Richard E. Lee (Polar Biology, 2008)

Mapping and characterization of novel parthenocarpy QTLs in tomato - Benoit Gorguet; Pieter Martijn Eggink; Juan Ocaña; Aparna Tiwari; Danny Schipper; Richard Finkers; Richard G. F. Visser; Adriaan W. van Heusden (Theoretical and Applied Genetics, 2008)

Lithospheric controls on the formation of provinces hosting giant orogenic gold deposits - Frank P. Bierlein; David I. Groves; Richard J. Goldfarb; Benoit Dubé (Mineralium Deposita, 2006)

An EST resource for cassava and other species of Euphorbiaceae - James V. Anderson; Michel Delseny; Martin A. Fregene; Veronique Jorge; Chikelu Mba; Camilo Lopez; Silvia Restrepo; Mauricio Soto; Benoit Piegu; Valerie Verdier; Richard Cooke; Joe Tohme; et al. (Plant Molecular Biology, 2004)